Sequential HLA‐haploidentical transplantation utilizing post‐transplantation cyclophosphamide for GvHD prophylaxis in high‐risk and relapsed/refractory AML/MDS. Issue 12 (2nd October 2018) - Fraccaroli, Alessia; Prevalsek, Dusan; Fritsch, Susanne; Haebe, Sarah; Bücklein, Veit; Schulz, Christoph; Hubmann, Max; Stemmler, Hans‐Joachim; Ledderose, Georg; Hausmann, Andreas; Schmid, Christoph; Tischer, Johanna
Abstract: This study evaluates the role of sequential therapy in HLA‐haploidentical transplantation (haplo‐HSCT) of high‐risk, relapsed/refractory AML/MDS. We analyzed the course of 33 adults with active disease at time of transplantation (AML n  = 30; MDS n  = 3; median age 58 years, range: 32‐71). Sequential therapy consisted of cytoreductive chemotherapy (FLAMSA n  = 21; clofarabine n  = 12) applied shortly prior to reduced intensity conditioning for T‐cell‐replete haplo‐HSCT using post‐transplantation cyclophosphamide as GvHD prophylaxis. No graft rejection was observed. Complete remission at day +30 was achieved in 97% of patients. CI of acute GvHD grade II‐IV and chronic GvHD was 24% (no grade IV) and 23%, respectively. NRM at 1 and 3 years was 15%, each. Severe regimen‐related toxicities (grade III‐IV) were observed in 58%, predominantly involving the gastrointestinal tract (diarrhea 48%, mucositis 15%, transient elevation of transaminases 18%). Probability of relapse at 1 and 3 years was 28% and 35%. At a median follow‐up of 36 months, the estimated 1‐ and 3‐year overall survival was 56% and 48%. Disease‐free survival was 49% and 40%, respectively. At 3 years, GvHD and relapse‐free survival (GRFS) was 24% while chronic GvHD and relapse‐free survival (CRFS) was 29%. Thus, our results indicate that sequential haplo‐HSCT is an effective salvage treatment providing high anti‐leukemic activity, favorable tolerance, and acceptable toxicity in patients suffering from advanced AML/MDS.